2016
DOI: 10.3727/096368915x689622
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials with Mesenchymal Stem Cells: An Update

Abstract: In the last year, the promising features of mesenchymal stem cells (MSCs), including their regenerative properties and ability to differentiate into diverse cell lineages, have generated great interest among researchers whose work has offered intriguing perspectives on cell-based therapies for various diseases. Currently the most commonly used adult stem cells in regenerative medicine, MSCs, can be isolated from several tissues, exhibit a strong capacity for replication in vitro, and can differentiate into ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
936
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,185 publications
(986 citation statements)
references
References 138 publications
5
936
0
9
Order By: Relevance
“…[11][12][13] Recently numerous clinical trials have shown that naive human mesenchymal stem cells (MSCs) are safe and beneficial to be considered for design of treatment methods for various pathologies. [14][15][16] The primary mechanism of their therapeutic effects is via secretion of paracrine factors under abnormal and diseased cellular environments. For example, the paracrine action of human MSC has been demonstrated to prevent cell death and induce proliferation of endogenous progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Recently numerous clinical trials have shown that naive human mesenchymal stem cells (MSCs) are safe and beneficial to be considered for design of treatment methods for various pathologies. [14][15][16] The primary mechanism of their therapeutic effects is via secretion of paracrine factors under abnormal and diseased cellular environments. For example, the paracrine action of human MSC has been demonstrated to prevent cell death and induce proliferation of endogenous progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs, as one of the most studied type of stem cells, have proven their therapeutic effects in researches and clinical trials [3,[20][21][22][23]. Stem cell therapy often encounters reduced viability after implantation in the injured tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal Stem Cells (MSCs) are under intense studies for clinical cell therapy because of their availability, immunosuppressive properties and ability to differentiate into many cell types [2][3][4][5]. MSCs, based on International Society for Cellular Therapy (ISCT) definition, should have three characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These candidate cells have some common features, including the secretion of bioactive factors with a protein structure known as paracrine mechanism [20]. Paracrine factors secreted from MSCs contain a rich source of valuable bioactive factors, including angiogenesis-related factors, vascularization-specific factors, and neuroprotective factors [21].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…According to evidence obtained from previous studies, MSC could be used to treat a variety of diseases, including hematological pathologies; Graft-versus-host disease (GvHD); cardiovascular disease; neurological disease; bone and cartilage disease; liver, lung, and kidney injuries;chronic inflammatory and autoimmune diseases; and urological disease [20,24].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%